Kompetensi Pegawai, Motivasi Kerja, Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Pertanahan Kabupaten Kediri - Wijaya, Tirta; Rahmawati, Zulfia (Universitas Islam Kadiri, 2025)
This study aims to analyze the effect of employee competence, work motivation, and organizational culture on employee performance at the Land Office of Kediri Regency. A quantitative method was used with regression analysis through SPSS. Data were collected using questionnaires distributed to employees. The results show that employee competence, work motivation, and organizational culture have a positive and significant effect on employee performance. Individually, employee competence, work motivation, and organizational culture each have a significant impact on employee performance. These findings confirm that improving employee competence, providing appropriate motivation, and strengthening a positive organizational culture can be effective strategies to enhance employee performance at the Land Office of Kediri Regency.